Diabetic Retinopathy in Tessellated Fundus - Pokharel, S; Sherpa, D; Shakya, K; Shrestha, R; Malla, O K; Pradhananga, C L; Pokhrel, R P (Journal of Nepal Health Research Council, 2014)
Background: Duration of diabetes, poor control, age of the patient, frequent hypoglycemia, hypercholesterolemia, over-weight, smoking, alcohol, renal failure and pregnancy have all been suggested as factors which may influence the onset of diabetic retinopathy.However, there are cases without retinopathy in spite of duration of 30 to 40 years of diabetes and presence of one or other above mentioned risk factors, suggesting role of local factors to prevent angiopathy.Our study aims to assess whether tessellated fundus is a protective factor for diabetic retinopathy.Methods: This was hospital based descriptive study. The patients included in the study were40 years and above having diabetes for 10 years and beyond. Diabetic retinopathy was graded following Early treatment Diabetic retinopathy Study.Results: Tigroid fundus was negatively associated with diabetic retinopathy (OR 0.49 with 95% confidence interval 0.21-1.11) and maculopathy (OR 0.43 with 95% confidence interval 0.15-1.3). Age 40-50 years (OR 0.67 with 95% confidence interval 0.24-1.83), female gender (OR 0.71 with confidence interval 0.31-1.61), HbA1c <6.5(OR 0.36 with confidence interval 0.99-1.31) and duration 10-15 years of onset of diabetes (OR 0.58 with confidence interval 0.22-1.37) was negatively associated with diabetic retinopathy in tigroid fundus diabetics. Age 40-50 years (OR 2.12 with confidence interval 0.43-10.5), female gender (OR 2.51 with confidence interval 0.38-10.88), HbA1c<6.5 (OR 3.12 with confidence interval 0.59-16.58) and duration 10-15 years of onset of diabetes (OR 1.5 with confidence interval 0.1-18.54) was positively associated with retinopathy in non-tigroid fundus.Conclusions: Tessellated fundus was observed as decreased risk for the development of diabetic retinopathy and maculopathy.Keywords: maculopathy;non-tessellated fundus;retinopathy; tessellated fundus.